The Effected of Curcuma to Dysmenorrhea: A Systematic Review - Mukhoirotin; Herin Mawarti; Siti Urifah; Hamimatus Zainiyah (Universitas STRADA Indonesia, 2024)
Background: Dysmenorrhea or menstrual pain is a common health problem among reproduction women. The prevalence of dysmenorrhea was high in many countries including in Indonesia. Some previous studies showed that curcumin was effective reduced menstrual pain. Purpose: The aim of this study was to determine the effected of curcumin to dysmenorrhea. Method: This study used systematic review method with Randomize Control Trial (RCT) design. The data was collected by using electronic databases such as Google Scholar, Science Direct, Pubmed, Scopus, Web of Science, SpringerLink and EBSCOhost in last 10 years, or in 2013-2023. The keywords used curcumin, turmeric, curcuma longa, dysmenorrhea, menstrual pain. Results: There were 7 selected articles in this literature study. Curcumin reduced intensity and duration of dysmenorrhea; the increasing of vitamin D; the reducing of serum IgE, serum aspartate transaminase (AST) and direct bilirubin levels among women with dysmenorrhea. Conclusion: Curcumin was affected to reducing the severity and symptoms of dysmenorrhea.